E-Government Research Policy and Management - , Donald Norris (IGI Publishing, 2008)
Virtual technology is increasingly prevalent in all spheres of daily life, including infiltration into governmental policies, processes, infrastructures, and frameworks. E-Government Research: Policy and Management provides scholars and practitioners with a critical mass of research on the integration, management, implications, and application of e-government. Covering such issues as e-government adoption and diffusion; social and performance issues of e-government; and information security, privacy, and policy, this book is an essential resource to any library collection.